V.O2 response profiles in severe intensity exercise - Hill, D. W.; Stevens, E. C. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: V.O2peak can be achieved over the range of intensities that define the severe intensity domain. The purpose of this study was to help characterize the V.O2 response during constant-load exercise in this domain. Methods: Twelve participants performed cycle ergometer tests at 267±52 W, 238±45 W, and 216±37 W, which were individually selected to elicit V.O2peak and to cause fatigue in ~3 min, ~5 min, and ~7 min, respectively. Results: Times to fatigue were 201±16 s, 301±20 s, and 448±51 s, respectively. V.O2 responded faster at higher work rates, with V.O2peak reached after 154±25 s, 193±35 s, and 206±24 s, respectively. Extrapolation of the times to reach V.O2peak revealed that 300 W was the highest power, and 151 s was the shortest time, for which V.O2peak could be elicited. TheV.O2 response was described using a three-component model. Exercise intensity did not affect the speed of the primary response, with time constants of 22±3 s, 23±4 s, and 23±4 s, respectively. However, the size of the primary phase was greater at higher intensities, with amplitudes of 1 798±200 ml.min-1, 1 739±267 ml.min-1, and 1 677±254 ml.min-1, respectively. The amplitude of the slow component was correspondingly smaller at higher intensities. Extrapolation of the slow component amplitudes revealed that 299 W was the highest intensity, and 152-153 s was the shortest time, for which a slow component would be engendered. Conclusion: V.O2peak is attained faster at higher intensities because the amplitude of the primary response is greater, not because the response is faster. There is a slow component to the V.O2 response at all intensities within the severe domain, but not at higher intensities, in the extreme domain, where fatigue occurs before V.O2peak can be elicited.